Reviewer Acknowledgements: Bridging Science, Care, and Community – GHMJ (Global Health Management Journal), Volume 8, Number 2, 2025 - GHMJ (Global Health Management Journal) (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
As the GHMJ (Global Health Management Journal) continues to advance integrated solutions for global health challenges, this edition highlights cutting-edge research and innovations spanning from molecular science to health systems strengthening. This issue of the Global Health Management Journal (Vol. 8, No. 2, 2025) presents an interconnected range of studies that reflect the dynamic challenges and innovations in global health. Beginning with clinical and pharmacological research, the issue highlights a study on radiographic patterns in tuberculosis patients with and without diabetes (Fatihah et al., 2025)—a dual burden increasingly relevant in both endemic and developing contexts. This clinical insight is followed by two experimental studies on plant-based therapies: one evaluating the hypoglycemic effect of bay leaf and celery extract in diabetic rats (Laorenz et al., 2025), and another investigating the antiviral potential of cassava leaf-derived nicotiflorin against dengue virus serotype 1 (Yulianti et al., 2025), reflecting a growing interest in local bioresources as alternatives to conventional treatment. The issue then transitions into broader public health and educational themes. A study from Ghana examines the risks of adolescent pregnancy complicated by diabetes (Ameyaw et al., 2025), while orthopedic data from Indonesia compares healing outcomes in different types of tibial fractures post-ORIF (Sakinah et al., 2025), offering evidence to improve trauma recovery. A thoughtful paper from South Africa challenges the way we conduct educational research with students with disabilities (Muzite & Gasa, 2025), advocating for more inclusive and participatory approaches. From Thailand, we see how self-efficacy–based programs can significantly reduce fall risk among older adults (Sukaree et al., 2025), offering a preventive approach to managing geriatric health. Meanwhile, a retrospective study from Türkiye (Boğa, 2025) shifts the focus to acute care, identifying critical predictors of ICU admission among emergency patients—highlighting the importance of timely response systems within hospital settings. These health system perspectives are further reinforced by a report from Zimbabwe that emphasizes the foundational role of laboratory capacity in supporting diagnosis, surveillance, and treatment for HIV/AIDS and other diseases (Mayavo, 2025). The issue concludes with a photo essay that captures the human side of scholarship—tracing how digital connections sparked a decade-long journey of academic friendship and collaboration (Yeyentimalla et al., 2025). Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/GHMJ.08.02 Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Ph.D. Journal Managers Suyitno, M.PHM Maretalinia, M.A External Reviewers Witri Pratiwi, M.Kes. (Universitas Swadaya Gunung Jati, Indonesia) Tiar Masykuroh Pratamawati, M.M., M.Biomed. (Universitas Swadaya Gunung Jati, Indonesia) Tiisetso Chuene, M.PH (University of Limpopo, South Africa) Crossman Mayavo, Ph.D (Midlands State University, Zimbabwe) Prof. Dr. Atthawit Singsalasang (Nakhon Ratchasima Rajabhat University, Thailand) Prof. Dr. Benchaporn Sukprasert (Suranaree University of Technology, Thailand) Elmiawati Latifah (Universitas Muhammadiyah Magelang, Indonesia) Türker Karaboğa (Esenyurt Necmi Kadıoğlu State Hospital, Türkiye) Lasata Shrestha, M.PH. (University of Washington, United States) Emmanuel Ameyaw (Kwame Nkrumah University of Science and Technology, Ghana) We express our sincere gratitude to the reviewers who have generously contributed their time and expertise to this edition of the Global Health Management Journal. Their commitment to scholarly excellence and constructive peer feedback has helped ensure the integrity and impact of every article published. Eligible reviewers may be considered for future roles on our Editorial Board, and receive Exclusive Publishing Opportunity and the chance to publish Guest Editorial Papers at no cost. Simply register on our website and select the